PERCEPÇÃO DE MÃES DE CRIANÇAS ENTRE 0 A 3 ANOS DE VIDA SOBRE A ASSOCIAÇÃO ENTRE ESTIMULAÇÃO AMBIENTAL E O DESENVOLVIMENTO NORMAL ATENDIDAS NA UNIDADE DE SAÚDE ANTONIO CARLOS REIS, CIDADE OLÍMPICA - SÃO LUÍS/ MARANHÃO - Paula, Lila Isabel Câmara de (2012)
An approach to family environment and its stimulation for a better development of children between 0 and 3 years of age, considering the stimulation received from their household as minimum conditions to ensure sensorimotor, cognitive, language and social emotional development, thus creating assumptions which are important for learning, in addition to allowing their interaction with the social, cultural, physical and socio-moral environments. The objective of this study was to evaluate these children s mothers about the association between the environmental stimulation and the normal development of children attended at Unidade de Saúde Antonio Carlos Reis, a public health unit in Cidade Olímpica, São Luís, Maranhão, from October 2009 to March 2010, identifying mothers understanding level about environmental stimulation and development, as well as characterizing the household in which the live. We have performed a qualitative exploratory and descriptive research, with a population consisting of 15 mothers. The Medical Records of the Unit, the Semi-Structured Interview, the Participant Observation were the instruments for data collection, besides the home visit and the qualitative analysis of the speeches, which served to organize and form categories comprising each topic discussed. Among the results, we have found that most mothers were between 13 and 20 years of age, incomplete elementary school, without a partner and with a low-income wage, among others. According to the proposed objectives, it was possible to organize the discussed topics in categories, such as: Reactions of mothers related to pregnancy; Mothers evaluation about how to stimulate children s development at home; Major mothers difficulties; Mothers comprehension related to their household and Mothers perception about necessity of stimulation of their environment for a better development of their children. We consider that interdisciplinary practice and interdisciplinary studies could contribute to improve the level of interactions mother/child and mother/health Professional, with increasing adhesion levels and mothers participation in stimulating their children, and consequently, with a significant evolution in the psychomotor and neurological development, and children s quality of life.